Osteochondroma of the condyle: case report and a conservative alternative for surgical approach (Research, Society and Development, 2021)
Osteochondroma (OC) is one of the most common benign tumors of bone but is rarely found in the mandibular condyle. The aim of this case report is to demonstrate condylectomy through endaural approach (EA) as a conservative alternative for the treatment of the OC. A 60-year-old woman having an OC of 23 millimeters length in the mandibular condyle. The patient underwent a surgical procedure for tumor resection. To generate less morbidity, a conservative approach was performed.